Notes on Early Land Plants Today. 5. Validation of two Drepanolejeunea species - Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2012)
Drepanolejeunea evansii Bischler (1964) was intended to be a nom. nov. for Drepanolejeunea infundibulata A.Evans (=sensu Evans 1903). However, the latter was actually a valid combination with another taxon, Lejeunea infundibulata Spruce (1884), which Bischler (1964) also recognized. The fact that Evans misunderstood Spruce’s taxon does not make his combination invalid and he is definitely not describing a new taxon as Bischler suggested. Drepanolejeunea evansii is regularly recognized, but as Bischler (1964) only gave a description in French and did not give any valid Latin diagnosis, the name remains invalid. Drepanolejeunea fragilis Bischler (1964) was in a similar way intended as a nom. nov. for Drepanolejeunea araucariae A.Evans (=sensu A.Evans 1903). However, Evans made a valid new combination and never intended to describe a new taxon. Bischler only gave a description in French, and did not provide any Latin diagnosis.